2015
DOI: 10.1128/jvi.03043-14
|View full text |Cite
|
Sign up to set email alerts
|

Identification of Capsid Mutations That Alter the Rate of HIV-1 Uncoating in Infected Cells

Abstract: After viral fusion with the cell membrane, the conical capsid of HIV-1 disassembles by a process called uncoating. We recently utilized the cyclosporine (CsA) washout assay, in which TRIM-CypA-mediated restriction of viral replication is used to detect the state of the viral capsid, to study the kinetics of uncoating in HIV-1-infected cells. Here we have extended this analysis to examine the effects of p24 capsid protein (p24 CA ) mutations and cellular environment on the kinetics of uncoating in infected cell… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

9
97
0

Year Published

2015
2015
2021
2021

Publication Types

Select...
6
2

Relationship

1
7

Authors

Journals

citations
Cited by 62 publications
(106 citation statements)
references
References 46 publications
9
97
0
Order By: Relevance
“…5E and F). The mutants N74D, E45A, and Q63/67A uncoat more slowly than wild type in the CsA washout assay to various degrees (6,7). Q63/67A displays the greatest delay in uncoating compared to that of wild type, the N74D mutation yields the smallest effect on uncoating kinetics, and E45A is intermediate between these two mutants.…”
Section: Drug Susceptibility In Relation To Uncoatingmentioning
confidence: 92%
See 1 more Smart Citation
“…5E and F). The mutants N74D, E45A, and Q63/67A uncoat more slowly than wild type in the CsA washout assay to various degrees (6,7). Q63/67A displays the greatest delay in uncoating compared to that of wild type, the N74D mutation yields the smallest effect on uncoating kinetics, and E45A is intermediate between these two mutants.…”
Section: Drug Susceptibility In Relation To Uncoatingmentioning
confidence: 92%
“…From biochemical, microscopy, and cell-based assays, two viral factors have been implicated in uncoating: the CA protein and the process of reverse transcription. Mutations in CA can alter capsid stability and uncoating kinetics (1)(2)(3)(4)(5)(6). Inhibition of reverse transcription delays uncoating in infected cells, indicating that this process facilitates capsid disassembly (7,8).…”
mentioning
confidence: 99%
“…Previous studies have demonstrated a general association between the stability of CA cores and reverse transcription in infected cells (30)(31)(32)(33)(34)(35). According to the currently accepted models, viral cores exist in a metastable state in virions and "uncoat" in target cells as a result of reverse transcription (66).…”
Section: Fates Of Eccentric Hiv-1 Particles In Target Cellsmentioning
confidence: 99%
“…Optimal stability of the CA lattice and its timely uncoating have previously been proposed to be important for reverse transcription (28)(29)(30)(31)(32)(33)(34)(35). Nevertheless, higher-order CA structures must still exist in cells because the host restriction factor TRIM5 recognizes structural features that exist only in viral cores but not in individual CA monomers (36)(37)(38)(39).…”
mentioning
confidence: 99%
“…Uncoating initiates as early as 1 h after viral fusion and may not be completed until the virus docks with the nuclear pore (43,(56)(57)(58)(59). Uncoating is facilitated by the process of reverse transcription, in which the growing viral DNA forces the capsid to open (43,44,60). The ability of Vpx to act independently of uncoating would provide a means for the rapid degradation of SAMHD1, and the subsequent rise in dNTP levels would facilitate uncoating.…”
Section: Discussionmentioning
confidence: 99%